THE DRY MATTER ACCUMULATION IN THE WINTER WHEAT ONTOGENESIS ON THE CALCAREOUS CHERNOZEM UNDER MINERAL FERTILIZERS ACTION - Vitalie CIOCHINA; Vasile LUNGU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The statistical data on investments in Rivne region for 2010-2016 are analyzed and presented in terms of sources of financing: the state budget, local budgets, own funds of enterprises, loans and loans, foreign investments and other sources of financing. Correlation analysis of available data is carried out. It was found that the profit of private peasant farms has a high linear dependence on budget investments, own funds of enterprises, loans, as well as other sources of financing. Farmers, however, depended heavily on state budget funds, but more dependent on foreign funds than OSG. Research shows that the greatest problem of low productivity of agricultural land use has low ecological security. The structural and economic system of land resources use is discussed. Directions for effective functioning and economic stimulation of balanced use of agricultural lands are offered.